2019
DOI: 10.1007/s00784-019-03069-7
|View full text |Cite
|
Sign up to set email alerts
|

Toothpaste factors related to dentine tubule occlusion and dentine protection against erosion and abrasion

Abstract: Objectives To investigate the effect of toothpastes on dentine surface loss and tubule occlusion, and the association of toothpasterelated factors to each of the outcomes. Materials and methods One hundred and sixty human dentine specimens were randomly distributed into 10 groups, according to different toothpastes. The specimens were submitted to artificial saliva (60 min), citric acid (3 min), and brushing abrasion (25 s; totalizing 2 min in toothpaste slurries). This was repeated five times and two outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
2
9
0
2
Order By: Relevance
“…Although different results have been shown between surface loss and tubular occlusion promoted by dentifrices, the use of all tested desensitizing and anti-erosive products can be indicated and considered safe for the use by patients with risk of developing erosive wear, as the changes they caused in dentin were not greater than those observed in brushing with distilled water. Our results showed that dentifrices claiming to have an anti-erosive properties did not differ from those claiming to be desensitizers, which is in agreement with a previous investigation showing that desensitizing and anti-erosive promoted less dentin surface loss at different levels [11]. It could be suggested that the differences in formulations between these products are minimal, perhaps limited only to their active ingredients or uoride formulations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although different results have been shown between surface loss and tubular occlusion promoted by dentifrices, the use of all tested desensitizing and anti-erosive products can be indicated and considered safe for the use by patients with risk of developing erosive wear, as the changes they caused in dentin were not greater than those observed in brushing with distilled water. Our results showed that dentifrices claiming to have an anti-erosive properties did not differ from those claiming to be desensitizers, which is in agreement with a previous investigation showing that desensitizing and anti-erosive promoted less dentin surface loss at different levels [11]. It could be suggested that the differences in formulations between these products are minimal, perhaps limited only to their active ingredients or uoride formulations.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, these toothpastes could be suitable for preventing ETW as well, based on our low SL results. A study showed that the pH of Elmex Erosion (EE) was 4.7 [21], a similar value to what we observed; however, this study's results showed that a higher pH was associated with a lower SL and that a lower pH was not associated with SL. This relationship between pH and SL could explain the non-signi cant correlation between these two variables in our results.…”
Section: Discussionsupporting
confidence: 85%
“…When it comes to fluoride varnish, the main factor is fluoride, whose protective effect against dental erosion is generally attributed to the formation of a layer similar to calcium fluoride. 20 Observed at higher concentrations, they were associated with a lower percentage of a successful response.…”
Section: Discussionmentioning
confidence: 96%
“…A 100 ml of each of the media was used to fill glass bottles into which the bars were inserted and then covered with lids. The bottles were kept in an incubator (Grant OLS 200, Grant Instruments Cambridge Ltd., Shepreth, UK) at 37 °C for 24 h under constant slow shaking of 70 rpm [ 22 , 23 ]. This immersion time corresponds to 2.5 years of clinical exposure to these acids, which suggested that teeth are exposed to these acids three times/day with a duration of 30 s/exposure [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%